The natural history of Ebola virus in Africa - Xavier Pourrut (2018)
Several countries spanning the equatorial forest regions of Africa have had outbreaks of Ebola hemorrhagic fever over the last three decades. This article is an overview of the many published investigations of how Ebola virus circulates in its natural environment, focusing on the viral reservoir, susceptible animal species, environmental conditions favoring inter-species transmission, and how the infection is transmitted to humans. Major breakthroughs have been made in recent years but many outstanding questions must be dealt with if we are to prevent human outbreaks by interfering with the viral life cycle. © 2005 Elsevier SAS. All rights reserved.